Effects of push–pull injection–suction spacing on sand biocementation treatment - Omoregie, Armstrong Ighodalo; Ong, Dominic Ek Leong; Li, Phua Ye; Senian, Nurnajwani; Hei, Ngu Lock; Esnault-Filet, Annette; Muda, Khalida; Nissom, Peter Morin (Geotechnical research, 2023)
The process of ureolysis-driven biocementation is used to improve granular soils. The precipitation of calcium carbonate (CaCO 3 ) crystals results from the reactions of urease generated by ureolytic bacteria and chemical reagents, which strengthen or bind soil particles together. Using a lab-based scaled physical model, this study investigated the influence of selected spacing intervals (107, 214 and 321 mm) on the effectiveness of biocementation through the injection–suction or ‘push–pull’ approach. Polystyrene moulds were used to create soil specimens. These were then injected with six cycles of treatment solutions at the intervals stated. The compressive strengths and calcium carbonate contents of the biocemented soil specimens were measured after curing. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), Fourier transform infrared (FTIR) spectroscopy and effluent analysis (pH and ammonium measurements) were also performed. The biocemented soil specimens with different spacing intervals obtained compressive strengths of 2.53 ± 1.06 to 4.2 ± 2.3 MPa, while the calcium carbonate contents were from 2.78 ± 0.3 to 11.16 ± 1.5%. The elemental compositions and bonding of calcium carbonate precipitates in the biocemented soil were confirmed by EDS and FTIR spectra, while SEM micrographs revealed chip-like and irregular rhombohedral crystal forms. The results demonstrated that injection spacing had an effect on biocemented soil treated by microbially induced carbonate precipitation.